Sailing Approval Letter - Broto Priyono; Surnata Surnata; Driaskoro Budi; Muhammad Khairani (IWJ : Inland Waterways Journal, 2020)
The issuance of a Sailing Approval Letter is a process of supervision carried out by the Harbormaster of a ship leaving the port to ensure that the ship, ship crew and cargo have technically fulfilled the requirements of shipping safety and security as well as protection of the maritime environment. The approach method used in this research is juridical empirical and the research specification used is descriptive analytical. Data collection techniques used in this study are through interview and documentation guidelines. The result of this research is that the responsibility of the harbormaster is very heavy in ensuring the safety and security of shipping because the harbormaster is a government official at the port who has the highest authority to carry out and supervise the fulfillment of statutory provisions to ensure shipping safety and security. Understanding of the requirements for safety and security of shipping is a condition where safety and security requirements are met with regard to water transportation, ports, and the maritime environment.